The distributional impact of the crisis in Greece - Manos Matsaganis; Chrysa Leventi (University of Essex, Institute for Social and Economic Research (ISER), 2011)
The severe economic crisis affecting Greece is widely expected to have a significant social impact in terms of greater inequality and increased poverty. We provide an early assessment of whether (and to what extent) this is the case. More specifically, we distinguish between two inter-related factors: on the one hand, the austerity measures taken to reduce fiscal deficits; on the other hand, the wider recession. Using the European tax-benefit model EUROMOD we attempt to quantify the distributional implications of both. With respect to the austerity measures, we focus on the changes introduced in spring 2010 affecting income tax, pension benefits and public sector pay. With respect to the wider recession, we model the effects of rising unemployment and inflation, as well as of lower earnings for self-employed workers and for employees of private firms. In simulating the impact of these changes on the distribution of incomes (and in estimating how the total burden of the crisis is shared across income groups), we take into account tax evasion and benefit non take up. We end by discussing the methodological pitfalls and policy implications of our research.
Keywords: C81; H55; I3; 330; austerity; Greece; inequality; poverty; microsimulation; Öffentliche Schulden; Wirtschaftskrise; Soziale Lage; Einkommensverteilung; Armut; Simulation; Griechenland